Keefektifan Cinema Education Pada Pelatihan Keterampilan Pengambilan Keputusan Karir Pada Peserta: Effectiveness Of Cinema Education In Training Skills Making Decision Career In Participants - Kartini Ningsih; Karyanti Karyanti (Suluh: Jurnal Bimbingan dan Konseling, 2017)
The purpose of this study was to determine the effectiveness of cinema education services in career decision-making skills to improve career decision-making skills in SMK Al-Ishlah students. The design of this study uses Single Subject Design (SSD) with multiple treatments and is supported by a repeated measure model. The subjects of this study were eight students of class X of SMK Al-Ishlah Palangka Raya who indicated as students behaving lack of career decision-making skills tended to be low, moderate, and high from the basics observation phase, intervention 1, intervention 2, and intervention 3. Analysis data uses visual analysis by paying attention to changes in levels and trends. The results of the study showed that the eight subjects in the baseline phase had a lack of behavioural career decision-making skills that tended to be low. In the intervention phase, 1 using education cinema to eight subjects experienced an increase in categories from low to moderate categories.